Lasting mesothalamic dopamine imbalance and altered exploratory behavior in rats after a mild neonatal hypoxic event - Nikolic, Barbara; Trnski-Levak, Sara; Kosic, Kristina; Drlje, Matea; Banovac, Ivan; Hranilovic, Dubravka; Jovanov-Milosevic, Natasa (Frontiers in Integrative Neuroscience, 2024)
Adversities during the perinatal period can decrease oxygen supply to the fetal brain, leading to various hypoxic brain injuries, which can compromise the regularity of brain development in different aspects.To examine the catecholaminergic contribution to the link between an early-life hypoxic insult and adolescent behavioral aberrations, we used a previously established rat model of perinatal hypoxia but altered the hypobaric to normobaric conditions. Exploratory and social behavior and learning abilities were tested in 70 rats of both sexes at adolescent age. Inherent vertical locomotion, sensory-motor functions and spatial learning abilities were explored in a subset of animals to clarify the background of altered exploratory behavior. Finally, the concentrations of dopamine (DA) and noradrenaline in midbrain and pons, and the relative expression of genes for DA receptors D1 and D2, and their downstream targets (DA-and cAMP-regulated phosphoprotein, Mr 32 kDa, the regulatory subunit of protein kinase A, and inhibitor-5 of protein phosphatase 1) in the hippocampus and thalamus were investigated in 31 rats. A lesser extent of alterations in exploratory and cognitive aspects of behavior in the present study suggests that normobaric conditions mitigate the hypoxic injury compared to the one obtained under hypobaric conditions. Increased exploratory rearing was the most prominent consequence, with impaired spatial learning in the background. In affected rats, increased midbrain/pons DA content, as well as mRNA levels for DA receptors and their down-stream elements in the thalamus, but not the hippocampus, were found. We can conclude that a mild hypoxic event induced long-lasting disbalances in mesothalamic DA signaling, contributing to the observed behavioral alterations. The thalamus was thereby indicated as another structure, besides the well-established striatum, involved in mediating hypoxic effects on behavior through DA signaling.